Recent advances in Polygonatum sibiricum polysaccharides: structural insights, bioactivities in Vitro and in Vivo, and therapeutic potential in human and animal models – A review - Mohamed E. Abd El-Hack; Hassan A. Rudayni; Ahmed K Aldhalmi; Abdullah S. Alawam; Ahmed A. Allam; Mohammad M.H. Khan; Asmaa F. Khafaga (Carbohydrate Polymer Technologies and Applications)
Polygonatum sibiricum polysaccharides (PSPs) have attracted increasing attention due to their diverse biological activities and broad therapeutic potential. This review is presented as a comprehensive narrative review, based on a structured analysis of peer-reviewed literature published between 2000 and 2025, sourced from databases including PubMed, Web of Science, and Scopus. It summarizes recent advances in the structural characterization, extraction technologies, and bioactivities of PSPs based on both in vitro and in vivo studies. Various extraction methods such as hot water extraction, ultrasound-assisted extraction, enzyme-assisted extraction (using cellulase and papain), radiation-assisted extraction, and green solvents like natural deep eutectic solvents (NADESs) and CO₂-triggered hydrophilic solvents are critically compared. Quantitative data from optimized conditions show PSP yields ranging from 4.4 % (hot water) to 29.7 % (NADES-based extraction). Structural features including monosaccharide composition, glycosidic linkages, and molecular weight distribution are discussed in relation to pharmacological functions. PSPs demonstrate promising antioxidant, immunomodulatory, anti-diabetic, anti-obesity, hepatoprotective, and anti-tumoral effects. Clinical relevance is supported by evidence of improved immune response, glucose regulation, and lipid metabolism in preclinical disease models. Furthermore, PSPs hold potential for applications in the pharmaceutical, nutraceutical, and functional food industries due to their biocompatibility and therapeutic value. In conclusion, this review highlights the need for standardized extraction protocols, deeper investigations into structure activity relationships, and translational clinical research to advance the biomedical and industrial applications of PSPs.